Anthopleura mariscali, a new species of sea anemone (Cnidaria: Anthozoa: Actiniaria) from the Gal pagos Islands - Daly, Marymegan; Fautin, Daphne G. (Zootaxa, 2004)
Anthopleura mariscali, a new species of sea anemone (Actiniaria) known only from the intertidal zone of islands in the Gal pagos Archipelago, is described and illustrated. The column of a member of Anthopleura mariscali is orange to pink, becoming darker distally, and has prominent endocoelic marginal projections, each of which bears an acrorhagus on the oral surface and several verrucae on the adoral surface. Distally, the projections are typically frosted with opaque white patches. Living firmly adherent to the substratum in cracks and crevices, the animal is inconspicuous in life.